2015
DOI: 10.4161/19336950.2014.978676
|View full text |Cite
|
Sign up to set email alerts
|

Two-pore channel 1 interacts with citron kinase, regulating completion of cytokinesis

Abstract: Two-pore channels (TPC1, 2, and 3) are recently identified endolysosmal ion channels, but remain poorly characterized. In this study, we show for the first time a role for TPC1 in cytokinesis, the final step in cell division. HEK 293 T-REx cells inducibly overexpressing TPC1 demonstrated a lack of proliferation accompanied by multinucleation and an increase in G2/M cycling cells. Increased TPC1 was associated with a concomitant accumulation of active RhoGTP and a decrease in phosphorylated myosin light chain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
1
14
1
Order By: Relevance
“…Unlike previous studies that show a role for TPC isoforms in cell cycle regulation when overexpressed in HEK293 cells [6], silencing of endogenous TPC expression had no effect on MDA-MB-468 cell proliferation, highlighting differences between endogenous and overexpressing systems.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Unlike previous studies that show a role for TPC isoforms in cell cycle regulation when overexpressed in HEK293 cells [6], silencing of endogenous TPC expression had no effect on MDA-MB-468 cell proliferation, highlighting differences between endogenous and overexpressing systems.…”
Section: Discussioncontrasting
confidence: 96%
“…TPC1 and TPC2 silencing also had different effects on CPA-mediated changes in [Ca 2+ ] CYT . The gating and permeability of TPC1 and TPC2 vary [4] and examples of differential roles are also reflected in the effects of TPC isoform silencing on endomembrane dynamics [5], effects of overexpression on multinucleation [6], and roles on local and global Ca 2+ signals [25]. In light of previous studies indicating a role for TPC2 in store-operated calcium entry [26], future studies assessing the mechanism by which TPC2 remodels CPA-induced changes in [Ca 2+ ] CYT in this model are required, particularly in the context of calcium induced Ca 2+ release [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accord, studies have demonstrated functional requirements for TPCs in these very same processes (37,48,(72)(73)(74). Additional roles for TPCs have been identified in membrane trafficking (33,45,63), autophagy (46,49,75), nutrient sensing (53), exocytosis (35,76), angiogenesis (77), fertilization and embryogenesis (78), and cytokinesis (79). Importantly, recent work shows that TPCs are also involved in disease, including Parkinson's disease (80), fatty liver disease (59), and Ebola infection (81).…”
Section: Controversymentioning
confidence: 86%
“…Today it is known that TPCs have a role not only in ion signaling but also in intracellular vesicle trafficking, [18][19][20] participating in a wide range of pathophysiological processes; that is why in the last years TPCs have received an increased attention from the main journals in the field, and they have been related to the regulation of many biological functions at different levels, including pancreatic b-cell function, 21,22 thermogenesis, 23 nutrient sensing, 6 endolysosomal transport and functions, 19,20 exocytosis, 24,25 cytokinesis, 26 fertilization and embryogenesis, 27 cell differentiation, [28][29][30][31] angiogenesis, 32 endothelium activation mediated by histamine, 33 smooth muscle contraction, 34 autophagy, [35][36][37][38][39][40] skin pigmentation, 41 or even to the Ebola virus infection mechanism. 42 As well, recent studies have suggested their possible implication in the pathogenesis of Alzheimer disease, 36 46 Thus, TPCs have become attractive therapeutic targets, although it is necessary to go deeper into their main functions and mechanisms of action not only to clinically relevant compounds could be designed but also to understand the pathophysiology of an increased wide range of diseases related to TPCs function/dysfunction.…”
Section: Introductionmentioning
confidence: 99%